2002
DOI: 10.2337/diabetes.51.5.1601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the (C825T) Gβ3 Polymorphism on Adrenoceptor-Mediated Lipolysis in Human Fat Cells

Abstract: A common G␤ 3 gene polymorphism (C825T) influences G protein receptor-mediated signal transduction. We investigated whether this polymorphism influences lipolysis in isolated subcutaneous fat cells from 114 healthy obese subjects. The G␤ 3 protein content was markedly decreased in adipocytes of TT carriers, but the alternatively spliced short form of G␤ 3 previously shown in platelets of 825T carriers was not detected. Fat cells of TT carriers showed a significant 10-fold decrease in the half-maximum effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 21 publications
(28 reference statements)
1
42
0
1
Order By: Relevance
“…38 The observed genotype frequency for the polymorphism in the GNB3 gene was similar to that previously reported in other Caucasian populations. 26,31 Rydén et al 35 showed that the T variant of this polymorphism was associated with a blunted in vitro responsiveness for the non-selective ISO in abdominal subcutaneous adipocytes of male and female overweight subjects. In contrast with Ryden et al 35 we found a tendency toward a reduced lipolysis aney in male overweight subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…38 The observed genotype frequency for the polymorphism in the GNB3 gene was similar to that previously reported in other Caucasian populations. 26,31 Rydén et al 35 showed that the T variant of this polymorphism was associated with a blunted in vitro responsiveness for the non-selective ISO in abdominal subcutaneous adipocytes of male and female overweight subjects. In contrast with Ryden et al 35 we found a tendency toward a reduced lipolysis aney in male overweight subjects.…”
Section: Discussionmentioning
confidence: 99%
“…26,31 Rydén et al 35 showed that the T variant of this polymorphism was associated with a blunted in vitro responsiveness for the non-selective ISO in abdominal subcutaneous adipocytes of male and female overweight subjects. In contrast with Ryden et al 35 we found a tendency toward a reduced lipolysis aney in male overweight subjects. It should be mentioned that our sample has no adequate power to provide a conclusive result about a genotype effect for the C825T polymorphism in the GNB3 gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One portion of adipose tissue (∼1 g) from obese subjects (cohort 1) was immediately subjected to collagenase treatment and isolated fat cells were incubated in duplicate exactly as described [13]. In brief, diluted cells were incubated in an albumin-containing buffer (pH 7.4) for 2 h at 37°C with air as gas phase without (basal) or with increasing concentrations of either the natural catecholamine noradrenaline, the selective beta-1 adrenergic receptor agonist dobutamine or the selective beta-2 adrenergic receptor agonist terbutaline.…”
Section: Lipolysis Studiesmentioning
confidence: 99%